Hubungan Dukungan Keluarga dengan Tingkat Kecemasan pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di Rumah Sakit Umum Delia Kecamatan Selesai Kabupaten Langkat - Leny Suarni; Sri Wahyuni; Wirda Faswita (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
Chronic renal failure (GGK) is a clinical symptom due to a decline in kidney function that is chronic, kidney failure also causes death if not replacement therapy, due to failure of kidney function to maintain metabolism and electrolytes. Hemodialysis is one of the therapies for the replacement of kidney function, in addition there are substitute therapies such as dialisa peritones, and kidney transplants. The purpose of this study was to determine the relationship of family support to the level of anxiety in patients with chronic renal failure who underwent hemodialysis at Delia Hospital Desa Sei Limbat Kecamatan Selesai Kabupaten Langkat. The study was conducted at Delia Hospital Desa Sei Limbat Kecematan Selesai Kabupaten langkat in September to Februari 2022 with the method of sampling using purposive sampling method with the number of samples of 41 respondents. The results of this study obtained Chi square value of 0.000 with a significance value of p value of 0.00 <0.05 so H0 rejected and H1 accepted which means there is a relationship of family support with anxiety levels in patients with chronic renal failure who underwent hemodialysis at the Hospital Delia Kecamatan Selesai Kabupaten Langkat.